An expanded population of CD8dim T cells with features of mitochondrial dysfunction and senescence is associated with persistent HIV-associated Kaposi’s sarcoma under ART - Clutton, Genevieve T.; Weideman, Ann Marie K.; Goonetilleke, Nilu P.; Maurer, Toby (Frontiers in Cell and Developmental Biology, 2022)
HIV-associated Kaposi’s sarcoma (KS), which is caused by Kaposi’s sarcoma-associated herpesvirus, usually arises in the context of uncontrolled HIV replication and immunosuppression. However, disease occasionally occurs in individuals with durable HIV viral suppression and CD4 T cell recovery under anti-retroviral therapy (ART). The underlying mechanisms associated with this phenomenon are unclear. Suppression of viral infections can be mediated by CD8 T cells, which detect infected cells via their T cell receptor and the CD8 co-receptor. However, CD8 T cells exhibit signs of functional exhaustion in untreated HIV infection that may not be fully reversed under ART. To investigate whether KS under ART was associated with phenotypic and functional perturbations of CD8 T cells, we performed a cross-sectional study comparing HIV-infected individuals with persistent KS under effective ART (HIV+ KS+) to HIV-infected individuals receiving effective ART with no documented history of KS (HIV+ KSneg). A subset of T cells with low cell surface expression of CD8 (“CD8dim T cells”) was expanded in HIV+ KS+ compared with HIV+ KSneg participants. Relative to CD8bright T cells, CD8dim T cells exhibited signs of senescence (CD57) and mitochondrial alterations (PGC-1α, MitoTracker) ex vivo. Mitochondrial activity (MitoTracker) was also reduced in proliferating CD8dim T cells. These findings indicate that an expanded CD8dim T cell population displaying features of senescence and mitochondrial dysfunction is associated with KS disease under ART. CD8 co-receptor down-modulation may be symptomatic of ongoing disease.